Respostas
respondido por:
9
-11mn -[8mn-(6mn)]
-11mn - [2mn]
-11mn-2mn
-13mn
-11mn - [2mn]
-11mn-2mn
-13mn
respondido por:
2
Olá Lincoln,
- 11mn - [ 8mn - ( 7mn + mn - 2mn ) =
- 11mn - [ 8mn - ( 6mn )] =
- 11mn - [ 8mn - 6mn ] =
- 11mn - [ 2mn ] =
- 11mn - 2mn =
===>> - 13mn
Bons estudos ! ^^
- 11mn - [ 8mn - ( 7mn + mn - 2mn ) =
- 11mn - [ 8mn - ( 6mn )] =
- 11mn - [ 8mn - 6mn ] =
- 11mn - [ 2mn ] =
- 11mn - 2mn =
===>> - 13mn
Bons estudos ! ^^
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás